Potential spatial distribution of citrus HLB vector Diaphorina citri (Hemiptera: Liviidae) in the department of Tolima, Colombia - Araque, Wilson; Arévalo, Emilio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Huanglongbing, or HLB, is one of the most devastating diseases in citrus fruits and is found in different departments in Colombia. However, this disease has not yet been reported for the Department of Tolima, which is a significant domestic producer of citrus fruits. In order to present the spatial possible distribution possible of Diaphorina citri vector of the Candidatus liberibacter bacterium that causes citrus HLB in relation to the location of citrus production systems in the department of Tolima (Colombia), the geostatistical process of interpolation by the Inverse Method of Weighted Distance (IDW) was used to define the areas of greater and lesser prevalence of the vector, based on sample data, forming possible mobility routes of the bacteria. With the multitemporal analysis of the distribution of the vector in 2014, 2015 and 2016, this work provides cartographic elements to support the use and consultation of information on the process of phytosanitary monitoring of citrus HLB, defining strategic monitoring sites of the vector.